1966
DOI: 10.1029/jz071i011p02791
|View full text |Cite
|
Sign up to set email alerts
|

Effective atmospheric losses for 125-Mev protons in South Atlantic Anomaly

Abstract: Orbit calculations are carried out to evaluate the effective atmospheric densities for geomagnetically trapped 125‐Mev protons whose guiding centers mirror between 200‐ and 560‐km altitude in the South Atlantic anomaly. Such orbits are limited to the region of B‐L space L = 1.38 and 0.2043 < Bm < 0.2355 gauss. Calculated are the effective atmospheric densities and scale heights experienced by the particle and its guiding center. Rates of energy loss by ionization are also calculated, taking into account atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The calculational results ·of Heckman and Brady [1966] show that within the range of altitudes we are considering the effective atmospheric density scale heigHt lS not constant, but increases approximately in proportion to altitude. The proportionality factor depends on, and increases with, solar activity, and is demonstrated in Figure 4a.…”
Section: Verification Of Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculational results ·of Heckman and Brady [1966] show that within the range of altitudes we are considering the effective atmospheric density scale heigHt lS not constant, but increases approximately in proportion to altitude. The proportionality factor depends on, and increases with, solar activity, and is demonstrated in Figure 4a.…”
Section: Verification Of Orientationmentioning
confidence: 99%
“…[Heckman and Brady, 1966}. mIn Measurements of proton.flux scale heights via east-west asymmetry measurements in the anomaly thus can be directly compared with model atmospheric scale heights.…”
Section: Verification Of Orientationmentioning
confidence: 99%
“…Since the proton lifetimes are determined by energy losses to electrons and collisions with atmospheric nuclei, it is the average atmospheric density along a trapped particle trajectory that should best correlate with proton fluxes. Such calculations were first done by Heckman and Brady [12] and have been stressed recently by Lemaire et al [17]. Kern [18] extended the work of Ray [15] and showed that the trajectory averaged density, in a dipole field, is proportional to the mirror point density .…”
Section: Introductionmentioning
confidence: 97%
“…Proton lifetimes within the belts are determined primarily by energy losses to electrons and by collisions with atmospheric nuclei. Cornwell et al [11] and Heckman and Brady [12] computed the average atmospheric density for a model atmosphere. Dragt [13] extended these studies to provide the variation of trapped particle fluxes as a function of solar activity.…”
Section: Introductionmentioning
confidence: 99%
“…Their model fundamentally influenced radiation belt proton research for a number of years. Blanchard and Hess [1964;Hess, 1968] and others [Cornwall et al, 1965;Heckman and Brady, 1966;Dragt, 1971] subsequently used the Harris and Priester model to conclude that the inner-belt proton flux J varied inversely with density r, that is J(r) � r…”
Section: S07001mentioning
confidence: 99%